Harmonisasi Standar AMDK menurut SNI dan Standar Internasional - Sri Agustini , M.Si (Kementerian Perindustrian, 2017)
The harmonization on the National Standard for bottled drinking water for mineral water (SNI 3553:2015) and demineral water (SNI 6241:2015) against the regulatory requirements set by Minister of healt regulation number 492/2010 and International Bottled Water Association (IBWA,2015), and WHO guidelines for drinking water quality has been done. The objective was to identify the harmonisation among requirements and standard specification which apllied on the bottled drinking water. There were 2 distinc differentiation identified. There is different mandatory parameter between Minister regulation and SNI. The SNI is more stringent and protected than standard required by Minister regulation for microbial contaminant. The Minister regulation and IBWA requires Total coliform and E. coli must not be detectable in any 100 ml sample of drinking water, while SNI has set Total coliform, Total Plate count and Pseudomonas aeruginosa as requirement. Test result for the samples taken during surveillance showed that all of 8 samples which were sent to 3 different laboratories did not detected for Total coliform. Instead of E. coli, SNI requires Pseudomonas aeruginosa and Total plate count as mandatory requirement. Both SNI for mineral water, demineral water and Minister regulation have the same chemical requirements for those which have health concern, but for some parameter SNI more stringent than Minister regulation. SNI has not required hardness, aluminium and zinc those are mandotory parameter according to Minister regulation and IBWA. SNI has reqiured desinfection by product which were secondary parameter according to minister of health regulation, IBWA and WHO. No differentiation for physical properties identified between Minister regulation and SNI. Keywords: Bottled drinking water, SNI, Ministry of health regulation 492/2010, IBWA code of practice, WHO guidelines.